THE INTERRELATIONSHIP OF MUSIC AND POETRY IN FINE ARTS - Verma, Vinita (International Journal of Research -GRANTHAALAYAH, 2026)
Art is humanity's eternal companion. Art originated with humanity's arrival on Earth. Art evolved alongside human development. The field of art holds a vast treasure, and its manifestations are diverse. Art mirrors society, and its function is therefore to fully express social life within society. In the rhythms of poetry, the colors of painting, the rhythms of dance, and the notes of music, the soul awakens to its fundamental form and merges with the Supreme in nature.